Social and pedagogical practice of the nurse-preceptor: a case study - Verônica Caé da Silva (Online Brazilian Journal of Nursing, 2014)
Aim: To describe the pedagogical practice used by the nurse-preceptor with graduate nurse students. Method: Case study conducted in 2011, at São Francisco de Assis Hospital-School, with 14 nurse-preceptors who mentored students from the Anna Nery School of Nursing. We used official documents and interviews to collect qualitative, descriptive data and analyzed the thematic categories. EEAN/HESFA protocol CEP number 114/2010. Results: The teaching actions occurred mainly in nursing consultation and the nurse-preceptor hardly took part in the planning and evaluation of student activities. There was concern regarding the service organization and distribution of the number of students per sector. Discussion: The power relationship, the political dimension, and the dichotomy between theory and practice. Conclusion: The nurse-preceptor did not participate in all the constituent steps of pedagogical practice, but conducted activities requiring such participation.